Chiral aryl-copper(III) electrophiles: new opportunities in catalytic enantioselective arylations and domino processes. - Rousseaux, S; Vrancken, E; Campagne, J (2012)
"Chiral aryl cation" equivalents: The combination of diaryliodonium salts and catalytic amounts of chiral copper complexes provides facile access to "chiral aryl cation" synthons. These reagents offer new possibilities for asymmetric arylation reactions that initiate further domino processes.